PERANAN LAPORAN KEUANGAN DALAM RANGKA MEMBERDAYAKAN DAN MENGEMBANGKAN USAHA MIKRO KECIL DAN MENENGAH DI KABUPATEN SUKOHARJO - Djoko Sigit Gunanto (Jurnal Akuntansi dan Pajak, 2015)
This study aims to determine the accounting practices in the financial statements of Micro, Small and Medium Enterprises in Sukoharjo, as well as to determine the barriers that exist in the application of accounting financial statements in Micro, Small and Medium Enterprises and how to overcome these obstacles. While the method of this study used a qualitative approach with descriptive qualitative oriented. Data and information obtained from the UMKM in Sukoharjo and other secondary data sources.The results showed that the First, the application of existing financial statements in Sukoharjo still not up, a lot of UMKM only use simple remarks did not even make financial records at all, resulting in low utilization of accounting information in the development of UMKM. Second, barriers experienced by UMKM in applying the financial statements are ignorance about the benefits of the financial statements for business development, a lack of knowledge of the perpetrators of Micro, Small and Medium Enterprises in making financial reports, UMKM have not felt directly from the application of accounting financial statements. The fix takes the role of government and relevant parties to help UMKM implement the financial statements to empower their business. Keywords: Accounting, Financial Statements, UMKM